Three Ways to Assess Corruption: How to compare indicators?; Trois façons d'évaluer la corruption : comment comparer les indicateurs ? - Frédéric Lesné (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
By weakening the institutional frameworks through which economic agents interact, corruption constitutes a major obstacle to economic development. Because of its secretive nature, measuring this phenomenon has proven challenging. Numerous initiatives have nonetheless been launched in the past two decades with the objective to produce reliable measures of corruption. For a researcher, find a way through the "jungle" of corruption indicators is not always easy. Yet, a close look at the issue of corruption measurement is often an essential preliminary step to successfully apprehend corruption as an empirical research topic. The aim of this review is precisely to evaluate the main categories of indicators that have been used more of less interchangeably from the middle of the 1990s for the study of macro-determinants and consequences of corruption, namely the indicators based on expert assessments, indicators constructed from surveys capturing the perceptions and experiences of corruption from households or businesspeople, and composite indicators of corruption. This study focuses on multi-year global andregional indicators that provide comparable scores across countries and time.
Keywords: C82; O17; 330